An introduction to the Nikon creative lighting system - Hess, Alan (Peachpit Press, 2013)
The most important aspect of capturing a quality image isn't the camera you use, the aperture settings, the shutter speed, or the ISO–it's the light. With this ebook, you will learn how to enhance the light in your images by using the Nikon Creative Lighting System (CLS), which allows you to easily take great photos with natural-looking light using a flash either on or off camera. You'll learn how to wirelessly control the amount of light of the remote flashes right from the camera, control an unlimited number of flashes, and use the flashes in up to three different controllable groups. If you have a relatively recent model of a higher-end consumer Nikon camera and a Speedlight, chances are you are ready to go! Follow along with Alan and you will: Learn your way around all the components of the CLS system, including cameras, flashes, and flash accessories Develop an understanding of flash photography and learn the basics of getting the best results using Basic Flash, Fill Flash, and Sync Modes Master the mechanics of setting up multiple flashes to build up the light in an image Explore advanced flash setups, learning to control an unlimited number of remote flashes, and work with more complex lighting setups.